Evolución reciente de la fecundidad y de la estructura por edad de la población europea - Faus Pujol, María Carmen (Geographicalia, 2017)
We know that the European population has always been the pioneerin significant demographic changes. In Europe the strong demographic expansion began which gave to what is know as demographic transition. There has also been in Europe, but more recently, a return to a situation whereby the growth rate is nought in some countries, the global population is stagnant, and the proportion of elderly citizens is becoming greater. The key of this situation is based upon the decreasing tendency of fertility according the different countries.The complexity of the phenomenon in itself and the variety of cases which are presented make it very difficult to obtain an overall idea. A solid research in the evolution of fertility and age structure of the European population has to take into account the following facts: first to clarify what is understood by the European population, secondly what are the differences in behaviour of each country concerning fertility, an finally how its actual demographic structure affects fertility.
Keywords: Fertility; demographic transition; demographic structure; Europe.